Nutrición animal: Texto de formación universitaria - Roque Huanca, Bernardo (2023)
The text that is put for the consideration of the reader, in its digital, revised and corrected edition, has been prepared for academic purposes, for the training of veterinarians and/or zootechnicians, in the context of the Altiplano of Puno-Peru; however, it can serve as a reference for any reader interested in animal nutrition. It includes six thematic units: digestive physiology of animals, as one of the key nutritional processes, followed by energy (carbohydrates), lipids, proteins, minerals and vitamins, and an additional thematic unit on the evaluation of the chemical composition and calorimetry of the food.
Keywords: animal nutrition; energy; protein; minerals; vitamins